Variations in growth, longevity and natural mortality for the protogynous hermaphroditic eightbar grouper Hyporthodus octofasciatus between the Indian and Pacific Oceans - Wakefield, Corey; Williams, A.; Newman, Stephen; Bunel, M.; Boddington, D.; Vourey, E.; Fairclough, D. (Elsevier, 2015)
Increased fishing pressure on deep-water demersal fishes in relatively recent times highlights the need for a better understanding of their biology, demography and relative abundance. The eightbar grouper Hyporthodus octofasciatus is one of the largest species of Epinephelidae and is highly valued in relatively deep-water fisheries throughout the Indo-West Pacific region. Currently, information on the life history of H. octofasciatus is limited to the south-eastern Indian Ocean. We compared estimated life history parameters for H. octofasciatus from this region with the western central Pacific Ocean. Histological examination of gonads of H. octofasciatus from a wide length and age range (295-1740mm TL and 6-65 years) suggested that this species is a protogynous hermaphrodite in the Pacific Ocean, which is consistent with data for this species in the south-eastern Indian Ocean and its congeners. However, the maximum length (1740mm TL), asymptotic length (L8, 1912mm TL) and longevity (65 years) were much greater in the Pacific compared to the Indian Ocean (1509mm TL, 1166mm TL and 47-56 years), resulting in substantially different growth trajectories and a lower instantaneous rate of natural mortality in the Pacific Ocean (i.e., 0.06 vs 0.09 year-1). Such regional variations in life history traits across the Indo-Pacific need to be considered in assessments and management of H. octofasciatus stocks within and across jurisdictions.